The Evolution of VANET: A Review of Emerging Trends in Artificial Intelligence and Software-Defined Networks - Octavio Jose Salcedo Parra; Lewys Correa Sanchez; Jorge Gomez (IEEE Access)
This paper presents an in-depth look at the evolution of Vehicular Ad Hoc Networks (VANET) and their increasing importance in the development of Intelligent Transportation Systems (ITS). Emerging technologies that shape the future of VANET are discussed, focusing on artificial intelligence (AI) and software-defined networking (SDN) as key solutions to the challenges inherent in these dynamic networks. Applications of AI, including machine learning (ML), deep learning, and swarm intelligence, for improving security, traffic efficiency, and information management in VANET were examined. Routing challenges in these environments are discussed and SDN is presented as a viable solution. SDN protocols, controllers, and architectures are described, and their advantages and disadvantages in the context of VANET are analyzed. It provides a comprehensive overview of the current state of VANET, the emerging technologies driving them, and the challenges and opportunities presented by their continued development. The convergence of AI, SDN, and other key technologies is crucial for intelligent transportation, paving the way for safer, more efficient, and more connected driving.